The solution of an infinite system of ternary differential equations - G., Ibragimov; H., Qo'shaqov; I., Turgunov; Alias, I. A. (Publishing House of Lviv Polytechnic National University, 2022)
The present paper is devoted to an infinite system of differential equations. This system consists of ternary differential equations corresponding to 3×3 Jordan blocks. The system is considered in the Hilbert space l2. A theorem about the existence and uniqueness of solution of the system is proved.